Patient Care Management Teams: Improving Continuity, Office Efficiency, and Teamwork in a Residency Clinic - Hern, Tricia (The Accreditation Council for Graduate Medical Education, 2009)
BACKGROUND AND PROBLEM STATEMENT: The goals of the patient-centered medical home (PCMH) include the efficient and effective delivery of patient-centered care in the context of a continuity relationship. In residency training programs, competing demands on faculty, residents, and office staff create considerable challenge in demonstrating these vital attributes of the PCMH to residents. Given the emphasis on the PCMH, primary care residency programs need to strengthen the methods for teaching and modeling continuity, office efficiency, and team-based approaches to care. INTERVENTION: We designed and implemented a new system of “patient care management teams” in our family medicine residency and evaluated its impact on team members. Our quality improvement interventions included the creation of team structures linking faculty advisors and residents with patients, intrateam management of office tasks, and the implementation of multidisciplinary team meetings. EVALUATION: We surveyed faculty (n  =  11), residents/fellows (n  =  39), and staff (n  =  12) before and at 2 points after the patient care management team interventions, and we collected patient satisfaction data during the intervention time period. RESULTS: The intervention resulted in significant improvements in perceptions of continuity of patient care, office efficiency, and team communication before and after the team interventions. During a 2-year period, the greatest improvements were in the areas of office efficiency and continuity of care. Independent patient satisfaction scores correlated with patient care management team improvements. CONCLUSIONS: Team structures, streamlined team-based management of routine office tasks, and consistent and frequent multidisciplinary meetings can improve the sense of continuity, office efficiency, and team collaboration in primary care residency clinics.